Cell-Free Tumor DNA Dominant Clone Allele Frequency Is Associated With Poor Outcomes in Advanced Biliary Cancers Treated With Platinum-Based Chemotherapy. (6th June 2022) - Uson Junior, Pedro Luiz Serrano; Majeed, Umair; Yin, Jun; Botrus, Gehan; Sonbol, Mohamad Bassam; Ahn, Daniel H.; Starr, Jason S.; Jones, Jeremy C.; Babiker, Hani; Inabinett, Samantha R.; Wylie, Natasha; Boyle, Ashton W.R.; et al.
Abstract : PURPOSE: This investigation sought to evaluate the prognostic value of pretreatment of circulating tumor DNA (ctDNA) in metastatic biliary tract cancers (BTCs) treated with platinum-based first-line chemotherapy treatment. MATERIALS AND METHODS: We performed a retrospective analysis of 67 patients who underwent ctDNA testing before platinum-based chemotherapy for first-line treatment for metastatic BTC. For analysis, we considered the detected gene with highest variant allele frequency as the dominant clone allele frequency (DCAF). Results of ctDNA analysis were correlated with patients' demographics, progression-free survival (PFS), and overall survival (OS). RESULTS: The median age of patients was 67 (27-90) years. Fifty-four (80.6%) of 67 patients evaluated had intrahepatic cholangiocarcinoma; seven had extrahepatic cholangiocarcinoma, and six gallbladder cancers. Forty-six (68.6%) of the patients were treated with cisplatin plus gemcitabine, and 16.4% of patients received gemcitabine and other platinum (carboplatin or oxaliplatin) combinations, whereas 15% of patients were treated on a clinical trial with gemcitabine and cisplatin plus additional agents (CX4945, PEGPH20, or nab-paclitaxel). TP53, KRAS, FGFR2, ARID1A, STK11, and IDH1 were the genes with highest frequency as DCAF. The median DCAF was 3% (0%-97%). DCAF > 3% was associated with worse OS (median OS: 10.8 v 18.8 months, P = .032). Stratifying DCAF in quartiles, DCAF > 10% was significantly related to worse PFS (median PFS: 3 months, P = .014) and worse OS (median OS: 7.0 months, P = .001). Each 1% increase in ctDNA was associated with a hazard ratio of 13.1 in OS when adjusting for subtypes, metastatic sites, size of largest tumor, age, sex, and CA19-9. CONCLUSION: DCAF at diagnosis of advanced BTC can stratify patients who have worse outcomes when treated with upfront platinum-based chemotherapy. Each increase in %ctDNA decreases survival probabilities.